Spatial and Temporal Characteristics of Land Use and Land Cover Change in Lijiang River Basin During 2000—2020 - Zhang Junmin; Li Yuqiao; Rong Cheng (Shuitu baochi tongbao)
[Objective] The temporal and spatial differentiation of land use and land cover change of the Lijiang River basin during 2000—2020 was analyzed in order to provide a basis for spatial governance for coordinated human activities and ecological security. [Methods] Based on remote sensing information identification and GIS spatial analysis platform, expansion intensity, transition matrix and time-space statistics and spatial self-organization methods were used to study the changing laws of land use and landscape structure. [Results] ① The main landscape of the Lijiang River basin was forest land and cultivated land, accounting for more than 90% of the landscape area. During 2000—2020, the area change rate was less than 0.37%, and the expansion intensity was less than 3.59% per year, indicating that the watershed had high-quality landscape ecology resources and ecological capital to build an international tourism center. Besides, its landscape structure was stable, and water ecology was good. ② Construction land had the fastest growth and significant expansion. Its area increased by 163.41% during 2000—2020, of which the average annual expansion of Lingui New District was 37.79%. Urbanization was the main driving force for landscape type and structural changes, and the water ecosystem was well maintained. ③ The watershed landscape types were rich in diversity, the landscape distribution was balanced. The diversity and evenness index formed a high-value center in cities and towns and tourism centers, while in mountainous areas, it was a low-value continuous area. The connectivity was good, the mountainous area was the high value center and the town was the low value center. Human activities had a significant disturbance to the grassland shape and the surrounding area of the town (median area). [Conclusion] The watershed landscape index structure is affected by similar occurrence environment and differentiation factors and that has spatial agglomeration distribution characteristics. Urban expansion and tourism activities are the main drivers of the differentiation of the landscape pattern of the Lijiang River basin. Regional development is more suitable for centralized urbanization and decentralized tourism.